2016
DOI: 10.3390/md14010013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ultraviolet B-Induced Expression of the Proinflammatory Cytokines TNF-α and VEGF in the Cornea by Fucoxanthin Treatment in a Rat Model

Abstract: Ultraviolet B (UVB) irradiation is the most common cause of radiation damage to the eyeball and is a risk factor for human corneal damage. We determined the protective effect of fucoxanthin, which is a carotenoid found in common edible seaweed, on ocular tissues against oxidative UVB-induced corneal injury. The experimental rats were intravenously injected with fucoxanthin at doses of 0.5, 5 mg/kg body weight/day or with a vehicle before UVB irradiation. Lissamine green for corneal surface staining showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…On day 19, the mice were anesthetized with 2.5% Avertin (Sigma-Aldrich, St. Louis, MO, USA) at 400 mg/kg by intraperitoneal injection for tear ferning tests and ocular surface photography. The photographs were assessed later for ocular surface indexes, including smoothness, 28 opacity, 29 topography, and lissamine green stain 30 following the criteria used in previous publications. The mice were then killed to collect eyes with their periocular tissues for further analyses.…”
Section: Data Collection and Assessment Schedulementioning
confidence: 99%
“…On day 19, the mice were anesthetized with 2.5% Avertin (Sigma-Aldrich, St. Louis, MO, USA) at 400 mg/kg by intraperitoneal injection for tear ferning tests and ocular surface photography. The photographs were assessed later for ocular surface indexes, including smoothness, 28 opacity, 29 topography, and lissamine green stain 30 following the criteria used in previous publications. The mice were then killed to collect eyes with their periocular tissues for further analyses.…”
Section: Data Collection and Assessment Schedulementioning
confidence: 99%
“…Although relatively fewer studies of Fx on DN, several studies have reported bioactivities of Fx about inflammation inhibition and antioxidant properties, indicating its potential anti-diabetic role. In rat models, pretreatment with Fx inhibited UV-B radiation induced corneal disorders including evident preservation of corneal surface smoothness, downregulation of proinflammatory cytokine expression, and decrease of infiltrated polymorphonuclear leukocytes from UV-B induced damage [31]. The combination of Fx and rosmarinic acid improved antioxidant and anti-inflammatory profiles through the down-regulation of inflammasome components, such as NLRP3 and ASC, and increased Nrf2 and HO-1 antioxidant genes expression in HaCaT Keratinocytes [32].…”
Section: Discussionmentioning
confidence: 99%
“…After fixing the head, the left eye was covered. In a room devoid of light, the right eye of each mouse was exposed to wavelength of 310 nm using an ultraviolet lamp, and the intensity was 550 µW/cm 2 , lasting for 3 min for five consecutive days (Chen et al, ). After 36 hr of induction, the model was examined under a slit lamp and scored according to Dicky's grading criteria for edematous corneal turbid (Dickey, Cassidy, & Bouchard, ; the same below) and the model induction was judged for successful establishment.…”
Section: Methodsmentioning
confidence: 99%